2015
DOI: 10.5858/arpa.2013-0625-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of Targeted Next-Generation Sequencing for Inherited Disorders

Abstract: We have successfully demonstrated the feasibility of using the NGS platform to multiplex genetic tests for several rare diseases and the use of cloud computing for bioinformatics analysis as a relatively low-cost solution for implementing NGS in clinical laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 22 publications
1
39
0
1
Order By: Relevance
“…It covers 614 genes, including the vast majority of genes currently known to cause neurometabolic disease, hence sharing similarities with WES approaches but with the added advantage of more optimal coverage of targeted areas (Kammermeier et al , 2014). Indeed, coverage of targeted areas was similar or superior to that reported in other gene panels despite the large number of genes covered (Nemeth et al , 2013; Yohe et al , 2015). Moreover, the diagnosis rate in our study was comparable to, or higher than, that reported in similar approaches recently applied in other patient groups exhibiting phenotypic heterogeneity (Kammermeier et al , 2014; Sommen et al , 2016; Trump et al , 2016).…”
Section: Discussionsupporting
confidence: 70%
“…It covers 614 genes, including the vast majority of genes currently known to cause neurometabolic disease, hence sharing similarities with WES approaches but with the added advantage of more optimal coverage of targeted areas (Kammermeier et al , 2014). Indeed, coverage of targeted areas was similar or superior to that reported in other gene panels despite the large number of genes covered (Nemeth et al , 2013; Yohe et al , 2015). Moreover, the diagnosis rate in our study was comparable to, or higher than, that reported in similar approaches recently applied in other patient groups exhibiting phenotypic heterogeneity (Kammermeier et al , 2014; Sommen et al , 2016; Trump et al , 2016).…”
Section: Discussionsupporting
confidence: 70%
“…While targeted enrichment is becoming widely used to screen for polymorphisms within human genomic loci associated with cancers and inherited disorders (79), its uses for multiplex pathogen characterization are still not widespread and, to our knowledge, have never been applied to veterinary pathogens. Wylie et al (10) recently reported the development of a comprehensive probe library for pathogen diagnostics and discovery that holds tremendous potential.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of functionally critical and disease-causing mutations occur in protein-coding regions, most of the genome is noncoding and may contain overlooked pathogenic variants. Besides, the TNGS assay is insensitive to detection of copy number variation (CNV) and other structural variants [28,31]. In our study, 9 out of 11 high-risk cases were identified as having a recessive carrier mutation with concordant association, among which 2 even have confirmatory TMS results.…”
Section: Limitationmentioning
confidence: 73%
“…Furthermore, as far as the TAT of TNGS assay was concerned, we can now achieve a throughput for 20 samples in 5 days, comprising 2-day sample preparation, 2-day sequencing and analysis, and 1 day of confirmation and validation [28]. Because the primary screening rate is about 1:200, a maximum daily TMS screening throughput of 4000 could be processed in accordance with the TNGS assay.…”
Section: Proposition Of Screening-diagnosis Workflowmentioning
confidence: 99%